Obecność sacrum w przestrzeni domowej – na przykładzie Ruchu Szensztackiego w gminie Suszec - Kozik, Ewa (Studia Etnologiczne i Antropologiczne, 2023)
The purpose of this article is an anthropological and phenomenological description of religious experience among members of the Catholic vangelistic Schönstatt Movement, centered on the miraculous representation of Our Lady of Triflescence, which began its activity in 1914 on the initiative of Josef Kentenich, and which today develops on every continent by setting the task of joining religiosity with everyday life. The main religious practice of the Schönstatt Movementis to move chapels with copies of the miraculous picture from home to home. The text concerns the community of the Municipality of Suszec in Upper Silesia, where the author conducted field research, i.e. conversations with members of the Schönstatt Movement and participating observations in their parish. The reflection covers issues related to the mutual relations between the sacrum and the profanum and the way they are perceived by people associated with the Movement. In particular, attention is devoted to specific religious behavior resulting from the sense of the presence of the sacred in a space more strongly associated with the profane, i.e. athome. The accounts of Schönstatt Movement members and their attitudes towards this form of religiosity are presented. The text refers to the theories popular in the anthropology of religion and religious studies, which enable the recognition of the phenomenon of the sacred and a description of its features.